The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1103/physrevlett.119.235301
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Non-Abelian Magnetic Monopoles in a Quantum Impurity Problem

Abstract: Recently it was shown that molecules rotating in superfluid helium can be described in terms of the angulon quasiparticles [Phys. Rev. Lett. 118, 095301 (2017)]. Here we demonstrate that in the experimentally realized regime the angulon can be seen as a point charge on a 2-sphere interacting with a gauge field of a non-abelian magnetic monopole. Unlike in several other settings, the gauge fields of the angulon problem emerge in the real coordinate space, as opposed to the momentum space or some effective param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
(126 reference statements)
0
14
0
1
Order By: Relevance
“…This paves the way to studying the decay of angulon quasiparticles and other microscopic mechanisms of the angular momentum transfer in experiments on quantum liquids, with possible applications to phonon quantum electrodynamics [99]. Furthermore, the angulon instabilities have been predicted to lead to anomalous screening of quantum impurities [20] as well as to the emergence of nonabelian magnetic monopoles [100], which opens the door for the study of exotic physical phenomena in helium droplet experiments. Future measurements on isotopologues, such as CD 3 or ND 3 , would allow the variation of the molecular rotational constants without altering the molecule-helium interactions, thereby providing an additional test of the model.…”
Section: /2 Lm K0mentioning
confidence: 94%
“…This paves the way to studying the decay of angulon quasiparticles and other microscopic mechanisms of the angular momentum transfer in experiments on quantum liquids, with possible applications to phonon quantum electrodynamics [99]. Furthermore, the angulon instabilities have been predicted to lead to anomalous screening of quantum impurities [20] as well as to the emergence of nonabelian magnetic monopoles [100], which opens the door for the study of exotic physical phenomena in helium droplet experiments. Future measurements on isotopologues, such as CD 3 or ND 3 , would allow the variation of the molecular rotational constants without altering the molecule-helium interactions, thereby providing an additional test of the model.…”
Section: /2 Lm K0mentioning
confidence: 94%
“…(24), which describes the lowest levels of the impurity problem (18) in the limit of ω → ∞, can also serve as a new platform for studying the original N-anyon problem without the presence of the interaction potential W. Namely, instead of Eq. 17, if we define (31) with the same ω and λ as in the previous case, the emergent gauge field is given by Eq. (9).…”
Section: B a Toy Model For Free Anyonsmentioning
confidence: 99%
“…[29]. Here our main motivation is to define a physical Hamiltonian for a bipartite system such that the statistics gauge field emerges as a consequence of the interaction between the two subsystems [30,31]. In particular, due to its experimental feasibility, we consider a quantum impurity model.…”
Section: Introductionmentioning
confidence: 99%
“…2,[19][20][21][22][23] These studies show that monopoles' physics had mechanics like the fluid system's hydro dynamical vortex systems Searches for monopoles, with scientists all over the world, consisted of two categories experimentally typically: (1) detecting preexisting monopoles, (2) creating and detecting then new monopoles. [24][25][26][27][28][29][30][31][32][33] Mathematical techniques explored here to solve eigen value problem might set a precedence to abstract who listic observational physics with mathematical preciseness, applicable further to provable generalized quantum relativistic grand formalism. In this paper, Helmholtz decomposition fields are only considered to come up with general formalism, especially since research experimentation measurements with Ferrolens observational results have shown that magnetism is exclusively a dipole phenomenon, which in contrast to eclecticism, hence cannot be mono pole.…”
Section: Introductionmentioning
confidence: 99%